Integrating Asafo Companies for Sustainable Ocean and Coastal Heritage Management in Ghana - John Windie Ansah; Georgina Yaa Oduro; Rosabelle Boswell (Modern Africa)
African intangible cultural heritage (ICH) is a rich resource for identity, community and sociality. Heritage institutions such as the Asafo companies in Ghana, are traditional warrior groups that historically defended the state. Today, they are critical to coastal heritage management processes. This article reveals their contribution and argues that, while Asafo groups desire greater inclusion in heritage management, the national government of Ghana seeks to decentralize ocean governance processes. But, Asafo companies are complex groupings in which identity and “place,” matter. The article concludes that for a decolonial and sustainable ocean heritage management, the national government of Ghana needs to engage with Asafo companies to better understand them. In doing, so, the government will be better placed to support both a decolonial heritage conservation and ocean sustainability.